Quality of life of patients with different forms of hemophilia on the example of Nizhny Novgorod region - D. S. Fokina; O. V. Zhukova; S. A. Volkova; A. L. Khokhlov (Izdatelstvo OKI, 2024)
It is important for public health to monitor and improve the health indicators of the population using the system of patient's quality of life (HRQoL) assessment regardless of the nosology of the disease. The use of HRQoL assessment provides health authorities with a tool for additional analysis of the performance of health services and for making decisions about funding priorities. The definition of HRQoL is one of the decisive factors in the calculation of QALYs because it measures the effectiveness of medical treatment in terms of how much it prolongs and/or improves patients' lives. The aim of the study is to determine the QALYs of hemophilia patients in Nizhny Novgorod region by means of electronic questionnaire using the SF-36 questionnaire. Methods. A validated SF-36 short form questionnaire was used in the study, which was distributed to adult patients with hemophilia A, B and Willebrand's disease of Nizhny Novgorod region together with a short form of informed voluntary consent. Twenty-eight people participated in the questionnaire. Calculation of general and final indicators of the HRQoL was carried out according to the instructions for processing data obtained with the SF-36 questionnaire. Results. The lowest score among all respondents was for GH "General Health Status" with a mean value of 61.00, and the highest score was for PF "Physical Functioning" with a mean value of 81.43. The study revealed that the majority of the surveyed patients were receiving Emicizumab (42.86 %). After comparing the ranges of values of the final indicators of physical (PH) and mental (MN') health in patients with different forms of hemophilia, the highest values of HRQoL indicators are observed in patients with hemophilia B, and the highest range of extreme values - in patients with hemophilia A. Conclusion. Patients with different forms of hemophilia are determined to have satisfactory values of HRQoL indicators, as all the results obtained in the course of the questionnaire are above the average value of the indicators. Mean HRQoL scores in patients receiving emicizumab are at a similar level compared to patients receiving other LPs, and fluctuations in HRQoL scores in these patients are less marked than in the other patients with hemophilia A.